A People’s History of Structural Racism in Academia From A(dministration of Justice) to Z(oology) - Rahman, Susan; Sunder, Prateek; Jackson, Dahmitra (Open textbook library., 2022)
The contents of this book were developed under an Open Textbooks Pilot grant from the Fund for the Improvement of Postsecondary Education (FIPSE), U.S. Department of Education. However, those contents do not necessarily represent the policy of the Department of Education, and you should not assume endorsement by the Federal Government.